Peran dan Dukungan Keluarga dalam Pencegahan Stunting di Kelurahan Banyurip - Prajayanti, Hilda; Maslikhah, Maslikhah; Baroroh, Ida; Kartika Mantasti Hapsari, Restiana (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
Malnutrition problems in pregnant women can result in malnutrition in babies and young children with low birth weight, including stunting. Efforts to overcome stunting by maximizing posyandu. However, various studies show that the role of nutritional health education and counseling in posyandu still faces various obstacles, such as the delivery of information that is less than optimal and less comprehensive, as well as varying levels of knowledge among mothers of young children. Therefore, family support is very necessary to prevent stunting in Banyurip Village in Pekalongan. This nutritional problem can only be resolved if the community understands the problem and knows how to overcome it according to the conditions and circumstances of each region. public . This community service begins with an opening, introduction of the community service team, distribution of pre-test questionnaires related to stunting material, introduction of the material and questions and answers, and at the end the community present is given another questionnaire to evaluate the material provided. The level of knowledge before the participants received material related to family support in preventing pain was mostly poor (73%), but after being given education about the role and support of the family in preventing stunting, the post test results increased knowledge, namely the majority of participants had good knowledge (93%).